O Summa a Summei contra gentiles – Cartea I (Verbum. Revista de teologie catolică, 2025)
The article offers a comprehensive overview of one of Aquinasʼs most important works, with a predominantly philosophical character: Summa contra Gentiles. After a brief examination of Thomistic natural theology in the light of contemporary thought, assessing its ongoing relevance, the article exposes the biographical context in which the work was conceived and written, outlines its purpose and guiding methodological principles, also offering a tripartite thematic structure.
Keywords: natural reason; sensible things; existence; God; knowledge; demonstration